Tilt testing and what you should know about it - Experience with 835 consecutive patients with syncope of unknown origin. (1st May 2018) - Gemein, Christopher; Roos, Maike; Wolf, Anika; Hermann, Nils; Kelava, Augustin; Chasan, Ritvan; Weipert, Kay; Helmig, Inga; Bogossian, Harilaos; Hamm, Christian W.; Neumann, Thomas; Schmitt, Joern; et al.
Abstract: Background: Numerous tilt testing protocols with and without a preceding passive phase or the administration of nitrates have already been investigated. However, a truely standardized method for the investigation does not yet exist. Methods and results: A total of 835 consecutive patients who underwent tilt testing between January 2005 and March 2015 were included in this study. Results of a passive tilt test (PTT), a nitrate-stimulated tilt test (NSTT) with a preceding passive phase of 20 min, or an early nitrate-stimulated tilt test (ENSTT) without a preceding passive phase were compared and analyzed retrospectively in 735 patients. In addition, a further 100 consecutive patients were prospectively randomized 1:1 to compare NSTT and ENSTT. In the retrospective analysis, 38% of the patients in the ENSTT group had a positive test response compared with 45% in the NSTT group and only 27% in the PTT group (p = 0.0002). In the prospective study, 34% of the patients had a positive test response in the ENSTT group compared with 42% in the NSTT group (p = 0.537). The mean duration to a positive test response was significantly shorter in the ENSTT group (retrospective and prospective p < 0.001). The nitrate-stimulated groups did not differ significantly with respect to the hemodynamic characteristics of a positive test response (retrospective: p = 0.773; prospective: p = 0.086). Conclusion: Due to the rate of positive test response being comparable to other protocols and its significantly shorter test duration, nitrate-stimulated tilt testing without a preceding passive tilt test may be favored for use in a busy clinical practice.